Case report: Sulfasalazine-induced hypersensitivity - Kuchinskaya, Ekaterina M.; Chikova, Irina A.; Kostik, Mikhail M. (Frontiers in Medicine, 2023)
Drug-induced hypersensitivity syndrome (DiHS)/drug reaction with eosinophilia and systemic symptoms (DRESS) is a systemic inflammatory condition that is characterized by multisystemic involvement (liver, blood, and skin), heterogeneous manifestations (fever, rash, lymphadenopathy, and eosinophilia), and an unpredictable course; cases of DiHS/DRESS caused by sulfasalazine are rare in children compared to adults. We report a case of a 12-year-old girl with juvenile idiopathic arthritis (JIA) and sulfasalazine-related hypersensitivity who developed fever, rash, blood abnormalities, and hepatitis complicated with hypocoagulation. The treatment with intravenous and then oral glucocorticosteroids was effective. We also reviewed 15 cases (67% male patients) of childhood-onset sulfasalazine-related DiHS/DRESS from the MEDLINE/PubMed and Scopus online databases. All reviewed cases had a fever, lymphadenopathy, and liver involvement. Eosinophilia was reported in 60% of patients. All patients were treated with systemic corticosteroids, and one patient required emergency liver transplantation. Two patients (13%) died. A total of 40.0% of patients satisfied RegiSCAR definite criteria, 53.3% were probable, and 80.0% satisfied Bocquet's criteria. Only 13.3% satisfied typical and 20.0% atypical DIHS criteria from the Japanese group. Pediatric rheumatologists should be aware of DiHS/DRESS due to its similarities to other systemic inflammatory syndromes (especially systemic JIA, macrophage activation syndrome, and secondary hemophagocytic lymphohistiocytosis). Further studies of DiHS/DRESS syndrome in children are needed to improve its recognition and differential diagnostic and therapeutic options.